2018
DOI: 10.1007/s11661-018-4789-7
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Intergranular Corrosion Resistance and Copper Content in the Precipitate Microstructure in an AA6005A Alloy

Abstract: A positive correlation is observed between the amount of Cu incorporated in hardening precipitates and intergranular corrosion resistance in an artificially aged Cu-containing 6005A alloy. Three mechanisms have been identified to increase Cu absorption in hardening precipitates: by increasing aging temperature, by pre-deformation, and by slow cooling from solution heat treatment. These findings demonstrate the possibility for development of new processing routes to produce Cu-containing Al-Mg-Si alloys with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The present work confirms and supplements earlier results [14] showing a beneficial effect of predeformation on the IGC resistance of 6000 series alloys with low Cu content. Results revealed that deformation of the Cu containing 6005 and C28 alloys by rolling or stretching before aging significantly reduced the IGC susceptibility of these materials.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present work confirms and supplements earlier results [14] showing a beneficial effect of predeformation on the IGC resistance of 6000 series alloys with low Cu content. Results revealed that deformation of the Cu containing 6005 and C28 alloys by rolling or stretching before aging significantly reduced the IGC susceptibility of these materials.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, pre-deformation resulted in a higher amount of Cu locked into bulk precipitates than in the undeformed material. Hence, the results indicated a correlation between increased Cu absorption into precipitates, reduced Cu concentration at the grain boundaries and an improved IGC resistance [14]. The purpose of the present work is to further verify the effect of pre-deformation on the IGC resistance by examining a few 6000 series aluminium alloys with different Cu content and Si/Mg ratio.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…6xxx series aluminium alloys are highly suitable materials for the structural, building, machinery, marine (ocean ships) and automotive industry due to their good weldability, good strength/weight ratios, and excellent formability capabilities. Moreover, these alloys have recently been used in aircraft fuselages (such as the Airbus A380) due to their lower costs compared with conventional 2xxx series aluminium alloys …”
Section: Introductionmentioning
confidence: 99%